2008
DOI: 10.3802/jgo.2008.19.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Plasma proteomic analysis of patients with squamous cell carcinoma of the uterine cervix

Abstract: Objective: To compare plasma protein expression between patients with squamous cell carcinoma (SCC) of the cervix and normal controls. Methods: Plasma samples from patients with benign gynecological disease (normal cervix, n=6) and cervical cancer (SCC, n=6) were subjected to plasma proteomic analysis using two dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization mass spectroscopy (MALDI-MS). Western blotting and immunoturbidimetric assay were performed to validate the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…The studies reported that some proteins or protein families are commonly reported as being differentially expressed regardless of species, in vivo or in vitro conditions, tissues and organs, and experimental objective. Interestingly, some of the proteins which we examined in this study such as afamin, ceruloplasmin and transferrin have also been reported by proteomic studies to be differentially expressed in patients with squamous cell carcinoma of the cervix, ovarian cancer, nasopharyngeal carcinoma and in those with central nervous system damage [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…The studies reported that some proteins or protein families are commonly reported as being differentially expressed regardless of species, in vivo or in vitro conditions, tissues and organs, and experimental objective. Interestingly, some of the proteins which we examined in this study such as afamin, ceruloplasmin and transferrin have also been reported by proteomic studies to be differentially expressed in patients with squamous cell carcinoma of the cervix, ovarian cancer, nasopharyngeal carcinoma and in those with central nervous system damage [23][24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies, however, await evaluation by quantitative analyses using appropriate methods in sufficiently large study groups [26][27][28][29][30][31][32][33]. Of these many studies, two may highlight the importance of proper validation studies after a potential tumor marker candidate has been discovered [29,33].…”
Section: Clinical Applications Of Afamin Measurementmentioning
confidence: 99%
“…The functions of afamin have been investigated in epidemiologic studies, most of which were cancerrelated. Circulating afamin concentrations have been studied in various types of carcinomas including ovarian (Jackson et al, 2007), bladder , colorectal (Choi et al, 2013), gastric (Humphries et al, 1844), uterine cervix (Jeong et al, 2008), breast (Opstal-van Winden et al, 2011, as well as thyroid cancer (Song et al, 2013). In addition, recently it was found that afamin was strongly associated with the prevalence and development of metabolic syndrome (Kronenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 97%